2019
DOI: 10.1128/jvi.01815-18
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2 Contributes to Virus Spread and Immunopathology in the Airways of Murine Models after Coronavirus Infection

Abstract: Transmembrane serine protease TMPRSS2 activates the spike protein of highly pathogenic human coronaviruses such as severe acute respiratory syndromerelated coronavirus (SARS-CoV) and Middle East respiratory syndrome-related coronavirus (MERS-CoV). In vitro, activation induces virus-cell membrane fusion at the cell surface. However, the roles of TMPRSS2 during coronavirus infection in vivo are unclear. Here, we used animal models of SARS-CoV and MERS-CoV infection to investigate the role of TMPRSS2. Th1-prone C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
559
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 605 publications
(583 citation statements)
references
References 50 publications
15
559
0
9
Order By: Relevance
“…One can speculate that furin-mediated precleavage at the S1/S2 site in infected cells might promote subsequent TMPRSS2-dependent entry into target cells, as reported for MERS-CoV (Kleine-Weber et al, 2018;Park et al, 2016). Collectively, our present findings and previous work highlight TMPRSS2 as a host cell factor that is critical for spread of several clinically relevant viruses, including influenza A viruses and coronaviruses (Gierer et al, 2013;Glowacka et al, 2011;Iwata-Yoshikawa et al, 2019;Kawase et al, 2012;Matsuyama et al, 2010;Shulla et al, 2011;Zhou et al, 2015). In contrast, TMPRSS2 is dispensable for development and homeostasis (Kim et al, 2006) and thus constitutes an attractive drug target.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…One can speculate that furin-mediated precleavage at the S1/S2 site in infected cells might promote subsequent TMPRSS2-dependent entry into target cells, as reported for MERS-CoV (Kleine-Weber et al, 2018;Park et al, 2016). Collectively, our present findings and previous work highlight TMPRSS2 as a host cell factor that is critical for spread of several clinically relevant viruses, including influenza A viruses and coronaviruses (Gierer et al, 2013;Glowacka et al, 2011;Iwata-Yoshikawa et al, 2019;Kawase et al, 2012;Matsuyama et al, 2010;Shulla et al, 2011;Zhou et al, 2015). In contrast, TMPRSS2 is dispensable for development and homeostasis (Kim et al, 2006) and thus constitutes an attractive drug target.…”
Section: Discussionsupporting
confidence: 78%
“…SARS-CoV can use the endosomal cysteine proteases cathepsin B and L (CatB/L) (Simmons et al, 2005) and the serine protease TMPRSS2 (Glowacka et al, 2011;Matsuyama et al, 2010;Shulla et al, 2011) for S protein priming in cell lines, and inhibition of both proteases is required for robust blockade of viral entry (Kawase et al, 2012). However, only TMPRSS2 activity is essential for viral spread and pathogenesis in the infected host whereas CatB/L activity is dispensable (Iwata-Yoshikawa et al, 2019;Shirato et al, 2016;Shirato et al, 2018;Zhou et al, 2015).…”
Section: Sars-cov-2 Employs the Sars-cov Receptor For Host Cell Entrymentioning
confidence: 99%
“…Hoffman et al [25] recently demonstrated that initial spike protein priming by transmembrane protease serine 2 (TMPRSS2) is essential for entry and viral spread of SARS-CoV-2 through interaction with the ACE2 receptor [26,27]. The serine protease inhibitor camostat mesylate, approved in Japan to treat unrelated diseases, has been shown to block TMPRSS2 activity [28,29] and is thus an interesting candidate.…”
Section: Spike Protein-based Vaccinementioning
confidence: 99%
“…A non-critical SARS-CoV-2infected patient in South Korea received lopinavir/ritonavir (Kaletra; AbbVie) on the eighth day of admission, after which the clinical symptoms improved and the coronavirus load began to decrease until undetectable [77] . Animal models suggest that TM-PRSS2 (type II transmembrane serine protease) plays an important role in coronavirus transmission [78] . TMPRSS2 activates the S protein of highly pathogenic human coronavirus, which binds to the receptor ACE2 and enters host cells [30 , 42 , 78-80] .…”
Section: Protease Inhibitorsmentioning
confidence: 99%